Urinary Phenolic Metabolites Associated with Peanut Consumption May Have a Beneficial Impact on Vascular Health Biomarkers - Isabella Parilli-Moser; Inés Domínguez-López; Anna Vallverdú-Queralt; Sara Hurtado-Barroso; Rosa M. Lamuela-Raventós (MDPI AG, 2023)
Phenolic compounds in peanuts may moderate inflammation and endothelial function. Thus, the aim of this study was to evaluate the association of urinary phenolic metabolites (UPMs) with vascular biomarkers after peanut product consumption. A three-arm parallel-group randomized controlled trial was conducted in 63 healthy young adults who consumed 25 g/day of skin roasted peanuts (SRP), 32 g/day of peanut butter (PB), or 32 g/day of a control butter for six months. UPMs were analyzed by liquid chromatography coupled to mass spectrometry. Additionally, urinary eicosanoids, prostacyclin I2 (PGI2), and thromboxane A2 (TXA2) were determined using two competitive enzyme-linked immunosorbent assay kits. Consumers of SRP and PB presented significantly higher excretion of UPMs (enterodiol glucuronide (p = 0.018 and p = 0.031), 3-hydroxybenzoic acid (p = 0.002 and p < 0.001), vanillic acid sulfate (p = 0.048 and p = 0.006), p-coumaric acid (p = 0.046 and p = 0.016), coumaric acid glucuronide I (p = 0.001 and p = 0.030) and II (p = 0.003 and p = 0.036), and isoferulic acid (p = 0.013 and p = 0.015) in comparison with the control group. An improvement in PGI2 (p = 0.037) levels and the TXA2:PGI2 ratio (p = 0.008) was also observed after the peanut interventions compared to the control. Interestingly, UPMs with significantly higher post-intervention levels were correlated with an improvement in vascular biomarkers, lower TXA2 (r from −0.25 to −0.48, p < 0.050) and TXA2:PGI2 ratio (r from −0.25 to −0.43, p < 0.050) and higher PGI2 (r from 0.24 to 0.36, p < 0.050). These findings suggest that the UPMs with higher excretion after peanut product consumption could have a positive impact on vascular health.